First report of Neofusiccoccum vitifusiforme and presence of other Botryosphaeriaceae species associated with Botryosphaeria dieback of grapevine in Sicily (Italy) - Vincenzo MONDELLO; Sandra LO PICCOLO; Gaetano CONIGLIARO; Antonio ALFONZO; Livio TORTA; Santella BURRUANO (Phytopathologia Mediterranea, 2013)
Summary. Since 2007, when a grapevine decline caused by Lasiodiplodia theobromae was reported for the first time in Sicily, vines showing similar declining symptoms have been also found in other grape-growing areas of western and central Sicily. We report the result of a study on fungi associated with grapevine decline in Sicily, with particular regard to those belonging to the Botryosphaeriaceae. Four species were found to be associated with declining vines, namely Diplodia seriata, Lasiodiplodia sp., Neofusicoccum parvum and Neofusicoccum vitifusiforme, the latter species reported for the first time on Vitis vinifera in Italy.